Mercury, Lead, and Cadmium in the Muscles of Five Fish Species from the Mechraâ-Hammadi Dam in Morocco and Health Risks for Their Consumers - Mohammed Mahjoub; Soufiane Fadlaoui; Mohammed El Maadoudi; Youssef Smiri (Journal of Toxicology)
This study aims to assess the degree of metal contamination (mercury (Hg), cadmium (Cd), and lead (Pb)) in the muscles of five species of fish Esox lucius, Sander lucioperca, Micropterus salmoides, Lepomis macrochirus, and Scardinius erythrophthalmus, from the Mechraâ-Hammadi Dam between July 2017 and May 2018, and to conduct a risk assessment for human consumers. Trace metals were determined by Graphite Furnace Atomic Absorption Spectrometry for the Pb and the Cd and by Cold Vapor Atomic Absorption Spectrometry for the Hg. The results gotten from the study of the muscles of the different fish species show that the higher mean amounts of Cd and Hg were determined in E. lucius, and the maximum mean levels of Pb were detected in S. erythrophthalmus. Results suggested that demersal fishes inhabiting near the sediments and piscivorous fishes with higher trophic level were likely to accumulate higher trace metal concentrations. The general order of bioaccumulation of the trace metals measured in the muscles of the fish species is as follows: Hg > Pb > Cd. Therefore, the bioaccumulation of Hg in fish studied is more important than that of Cd and Pb. Furthermore, these concentrations are higher in summer than in winter for all trace metals. All the values of the trace metals in the muscle tissues are below the maximum limits recommended by the European Community (EC) N° 1881/2006. However, estimation of noncarcinogenic health risks by the target hazard quotient indicated no obvious noncarcinogenic risks to humans that consume those fishes (THQ < 1). Results of THQ and maximum safe consumption indicated that Hg may cause more harm to human by fish consumption especially for E. lucius and S. lucioperca. Therefore, reduced intake of carnivorous fishes should be promoted as part of a healthier diet.